2013
DOI: 10.1007/s10661-013-3551-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentration in deepwater rose shrimp species (Parapenaeus longirostris, Lucas, 1846) collected from the Marmara Sea Coast in Tekirdağ

Abstract: Zn, Cd, Cr, Hg, As (total), Cu, Pb, and Ni levels of the deepwater rose shrimp (Parapenaeus longirostris, Lucas 1846), which were collected from the Tekirdağ coast of the Marmara Sea, were evaluated. The Marmara Sea is the recipient of discharges from both land-based sources and the Black Sea Bosphorus stream. There are large numbers of anthropogenic activities in the coastal region of the northern Marmara Sea that include urban effluent, discharges from touristic resorts, agricultural runoff, fishing, and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Pure arsenic is rarely found in nature and is not very toxic, but it can be oxidized easily in humid air and become toxic by conversion to arsenic anhydride. Arsenic, which has four different oxidation steps, is mostly in the form of +3 and + 5 valences in nature [1,11,12].…”
Section: Arsenic and Arsenic Compoundsmentioning
confidence: 99%
“…Pure arsenic is rarely found in nature and is not very toxic, but it can be oxidized easily in humid air and become toxic by conversion to arsenic anhydride. Arsenic, which has four different oxidation steps, is mostly in the form of +3 and + 5 valences in nature [1,11,12].…”
Section: Arsenic and Arsenic Compoundsmentioning
confidence: 99%
“…Results indicated that the investigated samples were moderately contaminated with Ag, Cr and As, moderately to severely contaminated with Zn and Ni, and severely contaminated with Cu. 30 Our previous study conducted between 2011-2012, a study on marine pollution in the region identified Pb, As, and Cu levels above those permitted by the Turkish Food Codex in shrimp sample collected from the coasts of Tekirdağ 31 .In addition, another research is to determine the mercury, lead and cadmium accumulation in scads (Trachurustrachurus) caught in the near Tekirdag in the sea of Marmara in 1996. Fish sample average mercury contents were 0.029 ppm and average lead contents were 0.038 respectively.…”
Section: Heavy Metal Pollution In Surface Water Groundwater Sedimenmentioning
confidence: 99%
“…Pollutants are present even in the most remote areas of the planet. For instance, heavy metals and persistent organic compounds have been detected in deep sea invertebrates and polar mammals, respectively 3,4 .…”
Section: Introductionmentioning
confidence: 99%